Corporate Governance, Effectiveness of Internal Audit Function and Fraud in Islamic Banking in Indonesia - Naufal Al Baqir; Sulhani Sulhani (Association of Certified Fraud Examiners Indonesia Chapter, 2023)
This research explores the correlation between corporate governance and the effectiveness of internal audit functions in preventing fraud within Islamic banking in Indonesia. This study uses 53 observational data sourced from the annual reports of Islamic banking in Indonesia for the period 2010-2019. The data were analyzed using linear regression. The results of this study indicate that corporate governance has no effect on fraud, while the effectiveness of the internal audit function is able to reduce fraud in Islamic banking in Indonesia. The implication of this research is that Islamic banking is expected to consider the effectiveness of the internal audit function in its formation, so that internal audit performance in fraud prevention can be carried out optimally.